MORAL VALUES IN HIGHER EDUCATION. NARRATIVEBIOGRAPHICAL APPROACH ON MEMORABLE UNIVERSITY PROFESSORS - Porta, Luis (2012)
In this paper we present partial results of our ongoing research in a national university in Argentina. We intend to define a specific corpus associated to good teaching connected to training and teaching professional development from a biographical-narrative perspective. We also analyze categories linked to a moral perspective in teaching, a central component in teaching practices that impact the definition of a “memorable teacher” at university level. The research adopts a biographical-narrative approach. We interviewed teachers who had been previously identified as “examples of good teaching” by students. Our paper explains the relevance that the interviewed teacher gave to moral features to their memorable teachers when they were students.